Edge-locating coloring of graphs - Korivand, Meysam; Mojdeh, Doost Ali; Baskoro, Edy Tri; Erfanian, Ahmad (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
An edge-locating coloring of a simple connected graph G is a partition of its edge set into matchings such that the vertices of G are distinguished by the distance to the matchings. The minimum number of the matchings of G that admits an edge-locating coloring is the edge-locating chromatic number of G, and denoted by χ′L(G). This paper introduces and studies the concept of edge-locating coloring. Graphs G with χ′L(G)∈2, m are characterized, where m is the size of G. We investigate the relationship between order, diameter and edge-locating chromatic number. We obtain the exact values of χ′L(Kn) and χ′L(Kn − M), where M is a maximum matching; indeed this result is also extended for any graph. We determine the edge-locating chromatic number of the join graphs of some well-known graphs. In particular, for any graph G, we show a relationship between χ′L(G + K1) and Δ(G). We investigate the edge-locating chromatic number of trees and present a characterization bound for any tree in terms of maximum degree, number of leaves, and the support vertices of trees. Finally, we prove that any edge-locating coloring of a graph is an edge distinguishing coloring.